Treatment of Menopausal Symptoms When Hormone Therapy Is Contraindicated - Niskanen, Laura Maria; Kärkkäinen, Henna Johanna; Tuppurainen, Marjo Tiina (Seminars in Reproductive Medicine, 2025)
Menopausal symptoms, particularly vasomotor symptoms (VMS) and genitourinary syndrome of menopause (GSM), significantly affect women's quality of life (QoL). While menopausal hormone therapy (MHT) is the most effective treatment, contraindications such as estrogen-sensitive cancers and thromboembolic conditions limit its use for many women. This review explores alternative nonhormonal treatments, including pharmacological options like selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, gabapentin, clonidine, and neurokinin receptor antagonists (e.g., fezolinetant), alongside nonpharmacological approaches such as lifestyle modifications, cognitive-behavioral therapy, and acupuncture. These alternatives, though less effective than MHT, provide critical options for women unable to use hormonal therapies. Emerging treatments like fezolinetant demonstrate promise in reducing VMS by addressing the underlying pathophysiology, but safety concerns, such as hepatotoxicity, require ongoing monitoring. GSM management includes therapies such as vaginal estrogens, prasterone, and ospemifene, with tailored approaches necessary for cancer survivors. Emphasis is placed on individualized care, better patient education, and continued research into the safety and efficacy of these therapies to improve the QoL for postmenopausal women.
Keywords: fezolinetant; genitourinary syndrome of menopause; menopause; nonhormone therapy; vasomotor symptoms